Book reviews. Issue 1 (1st January 2019) - Somigli, Luca; Renga, Dana; Hill, Sarah Patricia; Griffith, Matthew; Brodesco, Alberto; Jansen, Monica; Brizio-Skov, Flavia; Bona, Stefano; Carpin, Alessandro
Futurist Cinema: Studies on Italian Avant-Garde Film, Rossella Catanese (ed.) (2018) Amsterdam: Amsterdam University Press, 258 pp., ISBN: 9789089647528, h/bk, €95.00Relazioni brutali: Genere e violenza nella cultura mediale, Elisa Giomi and Sveva Magaraggia (2017) Bologna: Il Mulino, 240 pp., ISBN: 9788815265296, p/bk, €45.00Luigi Ghirri and the Photography of Place: Interdisciplinary Perspectives, Marina Spunta and Jacopo Benci (eds) (2017) Oxford: Peter Lang, 303 pp., ISBN: 3034322267, p/bk, £45.00A Companion to Italian Cinema, Frank Burke (ed.) (2017) Malden, MA: John Wiley and Sons, 618 pp., ISBN: 9781444332285, h/bk, 195.00Italy Beyond Gomorrah: Roberto Saviano and Transmedia Disruption, Floriana Bernardi (2017) London and New York: Rowan & Littlefield, 127 pp., ISBN: 9781786600189, p/bk, £24.95Media Convergence and Deconvergence, Global Transformations in Media and Communication Research, Sergio Sparviero, Corinna Peil and Gabriele Balbi (eds) (2017) Cham: Palgrave Macmillan, 341 pp., ISBN: 9783319512884, p/bk, € 106.99Spaghetti Westerns at the Crossroads: Studies in Relocation, Transition and Appropriation, Austin Fisher (ed.) (2016) Edinburgh: Edinburgh University Press, 313 pp., ISBN: 9780748695454, p/bk, £24.99Orient (TO) Express: Film di viaggio, etno-grafie, teoria d'autore, Marco Dalla Gassa (2016) Sesto San Giovanni: Mimesis/Cinema, 426 pp., ISBN: 9788857534312, p/bk, € 30'Reading Practices in Experimental Narratives: A Comparative Perspective from Print to Digital Fiction in Modern Languages', Emanuela Patti (ed.) (2016) Journal of Romance Studies, Volume 16, Number 1, Spring